THE INFLUENCE OF INFLATION RATE ON IMPORT VOLUME OF FABRIC WITH RUPIAH EXCHANGE RATE AS MODERATING VARIABLE(A Case Study at PT. Apparel One Indonesia 1) - brilian wicaksono; Budi Prasetya; Erika Devie (JOBS (Jurnal Of Business Studies), 2019)
The research aims to analyze the influence of Inflation Rate on Import Volume of Fabric, the influence of Exchange Rate on Import Volume of Fabric, the influence of Exchange Rate on relationship between Inflation Rate and Import Volume of Fabric. This research was an explanatory research with quantitative approach. Multiple Linear Regression Analysis and Moderated Regression Analysis. Data used in this study were secondary data which were obtained by doing a literature study and observation, and collected from Bank of Indonesia and PT. Apparel One Indonesia 1 from January 2015-December 2018. The output from this research showed that the inflation rate significantly influenced the import volume of fabric. While exchange rate had no significant influence on the import volume of fabric. The other output explained that exchange rate can’t moderate the relationship between inflation rate and import volume of fabric in PT Apparel One Indonesia 1. However, simultaneously, the inflation rate and exchange rate significantly influenced the import volume of fabric in PT Apparel One Indonesia